Media literacy, curriculum and the rights of the child. Issue 2 (4th March 2022) - Cannon, Michelle; Connolly, Steve; Parry, Rebecca
ABSTRACT: Engaging with digital media is part of everyday living for the majority of children, yet opportunities to learn about, through and with media are denied many pupils in compulsory schooling. Whilst Media Studies in the UK is internationally reputed to be well established, changes made to the primary and secondary national curriculum in 2014 included removal of existing media study elements. We demonstrate what is lost by these actions in relation to the United Nations Rights of the Child and, in particular, the right of the child to express identity. We demonstrate how media literacy had previously been included in curriculum, enabling opportunities to address children's rights, and propose that the absence of media education is part of an overall trend of the non-prioritisation of children's rights in England and Northern Ireland. The paper calls for media literacy to be reintroduced into primary and secondary curriculum.